Kemitraan Pemerintah, Dunia Usaha, dan Masyarakat dalam Sektor Transportasi Publik - Febri Yuliani (Institut Transportasi dan Logistik Trisakti, 2015)
Human mobility has been started since time immemorial, the activities carried out by a variety of purposes, among others, to find food, looking for a better place to live, flee from the invasion of other people and so on. In the mobility often brings the goods or not carrying goods. Therefore diperluhkan tool as a means of transportation. This article describes how to build a partnership between government, business and society in the public transport sector. The method used is: a method literature. Aspects of efficiency resulting from the development of transport in order to increase total factor productivity, a major factor to determine the extent of the relationship between transport and the economy. This is the basis for determining whether an increase in the supply of transport can provide something that is meaningful to increased competition or increased economic growth, social and environmental sustainability. Problems funding needs huge investments for the development of the transport sector can be overcome if the funds were handed over to private sector development as an owner of capital, while the government as a component of regulators should be bold and assertive in policy-making that comes from the community.